2016
DOI: 10.1038/icb.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and innate immunity: the ‘unTolld’ story

Abstract: Toll-like receptors (TLRs) are a family of 13 receptors known as pattern-recognition receptors (PRRs) and have a key role in the innate immune response. The TLRs are activated by pathogen-associated molecular patterns (PAMPs) that are structurally conserved molecules present on the surfaces of bacteria and viruses. The activation of these TLRs by pathogens results in the downstream activation of genes involved in the production of proinflammatory factors. There is a lack of understanding on the mechanisms by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 121 publications
(202 reference statements)
0
12
0
Order By: Relevance
“…Self-healing of primary infections of P. chabaudi bloodstage malaria generates long-lasting immunity, which manifests itself as much lower parasitemias upon homologous rechallenge in comparison to the corresponding primary infections Wunderlich et al 2014). There is ample evidence that also genes involved in both innate and adaptive immunity are under complex epigenetic control including modifications of DNA methylation (Lim et al 2010;Rodriguez-Cortez et al 2011;Kondilis-Mangum and Wade 2013;Obata et al 2015;Hennessy and McKernan 2016). Insofar, it is rather surprising that protective vaccination and P. chabaudi infections induce changes in the DNA methylation of promoters of so many genes, most of them are related to regulation of transcription, but only very few genes can be related to any functions of the immune system inherent to the liver by gene set enrichment analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Self-healing of primary infections of P. chabaudi bloodstage malaria generates long-lasting immunity, which manifests itself as much lower parasitemias upon homologous rechallenge in comparison to the corresponding primary infections Wunderlich et al 2014). There is ample evidence that also genes involved in both innate and adaptive immunity are under complex epigenetic control including modifications of DNA methylation (Lim et al 2010;Rodriguez-Cortez et al 2011;Kondilis-Mangum and Wade 2013;Obata et al 2015;Hennessy and McKernan 2016). Insofar, it is rather surprising that protective vaccination and P. chabaudi infections induce changes in the DNA methylation of promoters of so many genes, most of them are related to regulation of transcription, but only very few genes can be related to any functions of the immune system inherent to the liver by gene set enrichment analyses.…”
Section: Discussionmentioning
confidence: 95%
“…However, understanding this effect at the single-cell level has important conceptual implications that offer new therapeutic strategies to desensitize innate immunity in epithelial tissues and potentially impede the progression of chronic inflammation. Furthermore, considering that both innate and adaptive immunity are subject to epigenetic regulation 27,47 and are both dominated by digital signaling events, we propose that epigenetic switching could be a general mechanism for limiting tissue-or organism-level inflammation during the immune response. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic state of cells is believed to result in variation in innate responses among chickens and can determine the resistance/susceptibility patterns to pathogens (Gou et al, 2012). DNA methylation and histone modifications are important epigenetic modifications involving the promoter regions of pathogen sensors or signalling pathways leading to either activation or suppression of a series of immune responses (Gou et al, 2012;Hennessy & McKernan, 2016). While profiling innate responses in Salmonella enterica serovar Enteritidis susceptible and resistant birds, one study identified higher DNA methylation levels in the promoter region of TLR4 and TLR21 and in an exonic CpG island of TLR2-1 in the susceptible chickens (Gou et al, 2012).…”
Section: Epigenetic Control Of Innate Immunitymentioning
confidence: 99%